Optimalisasi Sistem Charging Induktif Electric Vehicle Menggunakan Algoritma PID Berbasis ESP-32 - Ahmad Dani; M. Agung Irwansyah; Beni Satria (CV. Hawari, 2026)
The widespread adoption of electric vehicles (EVs) is hindered by the practicality and efficiency of charging infrastructure. Inductive wireless power transfer (WPT) offers a promising alternative, but its output stability is challenged by variations in air-gap distance, magnetic coupling, and load. This research aims to optimize the stability and dynamic response of an inductive EV charging system by implementing a Proportional-Integral-Derivative (PID) control algorithm on an ESP-32 microcontroller. The ESP-32 was selected for its computational capability, built-in Wi-Fi/Bluetooth connectivity, and cost-effectiveness. The study employs a laboratory-scale prototype with series-series compensation. A one-group posttest-only design was used, testing nine scenarios combining three air-gap distances (2, 4, 6 cm) and three resistive loads (10, 20, 30 Ω). System performance was evaluated based on steady-state error (SSE) and settling time (t_s). The results show that the PID control significantly reduced the SSE to below 3% across all tested conditions, representing an average error reduction of 89.6% compared to the open-loop system. The settling time for a step load change was 120 ms, demonstrating a fast dynamic recovery. The system also effectively compensated for lateral misalignment. The integrated Wi-Fi module enabled real-time remote monitoring. This study concludes that an ESP-32-based PID controller provides a stable, responsive, and connected control solution for inductive EV charging systems, offering a cost-effective alternative to more complex hardware platforms.